1999
DOI: 10.1128/jvi.73.7.5887-5893.1999
|View full text |Cite
|
Sign up to set email alerts
|

The Human Papillomavirus Type 16 E6 Gene Alone Is Sufficient To Induce Carcinomas in Transgenic Animals

Abstract: High-risk human papillomaviruses (HPVs) are the causative agents of certain human cancers. HPV type 16 (HPV16) is the papillomavirus most frequently associated with cervical cancer in women. The E6 and E7 genes of HPV are expressed in cells derived from these cancers and can transform cells in tissue culture. Animal experiments have demonstrated that E6 and E7 together cause tumors. We showed previously that E6 and E7 together or E7 alone could induce skin tumors in mice when these genes were expressed in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
99
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 219 publications
(106 citation statements)
references
References 42 publications
6
99
0
1
Order By: Relevance
“…A broad range of pathology, mostly restricted to the squamous epithelium, was observed in the K14-HPV16 mice as described previously (5)(6)(7)(8). Figure 1 shows a comparative phenotype of a wild-type FVB/N mouse and a K14-HPV16 transgenic mouse at 9 months of age.…”
Section: K14-hpv Type 16 Transgenic Micesupporting
confidence: 63%
See 4 more Smart Citations
“…A broad range of pathology, mostly restricted to the squamous epithelium, was observed in the K14-HPV16 mice as described previously (5)(6)(7)(8). Figure 1 shows a comparative phenotype of a wild-type FVB/N mouse and a K14-HPV16 transgenic mouse at 9 months of age.…”
Section: K14-hpv Type 16 Transgenic Micesupporting
confidence: 63%
“…Previous studies (5)(6)(7)(8) have clearly shown that the lesions in the K14-HPV16 transgenic mouse model show characteristic neoplastic progression in the squamous epithelium with advancing age. We examined biopsies from the ears of transgenic mice, since the ears consistently develop increasingly severe lesions, as described previously (5)(6)(7)(8) . Figure 2A shows the ear epithelium of an adult wild-type FVB/N mouse.…”
Section: K14-hpv Type 16 Transgenic Micementioning
confidence: 98%
See 3 more Smart Citations